2022
DOI: 10.1186/s13059-022-02643-9
|View full text |Cite
|
Sign up to set email alerts
|

Host-microbiome protein-protein interactions capture disease-relevant pathways

Abstract: Background Host-microbe interactions are crucial for normal physiological and immune system development and are implicated in a variety of diseases, including inflammatory bowel disease (IBD), colorectal cancer (CRC), obesity, and type 2 diabetes (T2D). Despite large-scale case-control studies aimed at identifying microbial taxa or genes involved in pathogeneses, the mechanisms linking them to disease have thus far remained elusive. Results To iden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 126 publications
0
11
0
Order By: Relevance
“…The abundance of Agathobacter rectalis (OTU 120) in ileum was negatively correlated with the expression of antimicrobial CXCL6 and chemokine CCL20 , so was the abundance of Streptococcus (OTU 37) and Eikenella (OTU 39) in rectum. A recent host-centered study has identified microbiome-derived protein clusters with high sequence identity to human protein-protein interactions (PPIs) by collecting existing interspecies PPIs data [170] . By combining PPIs with metagenome analysis, host functional annotations were added to microbiome-related diseases such as IBD, so as to provide a more reliable reference for the study of disease mechanism and promising therapeutic molecular targets.…”
Section: Multi-omics Integration Launches a New Era Of CD Researchmentioning
confidence: 99%
“…The abundance of Agathobacter rectalis (OTU 120) in ileum was negatively correlated with the expression of antimicrobial CXCL6 and chemokine CCL20 , so was the abundance of Streptococcus (OTU 37) and Eikenella (OTU 39) in rectum. A recent host-centered study has identified microbiome-derived protein clusters with high sequence identity to human protein-protein interactions (PPIs) by collecting existing interspecies PPIs data [170] . By combining PPIs with metagenome analysis, host functional annotations were added to microbiome-related diseases such as IBD, so as to provide a more reliable reference for the study of disease mechanism and promising therapeutic molecular targets.…”
Section: Multi-omics Integration Launches a New Era Of CD Researchmentioning
confidence: 99%
“…In the case of bacteria, 25-50% of the genome comprises HPs, which may have roles in disease and therapeutic targets because they are involved in the pathogenesis of a disease or the regulation of a biological pathway [20]. Hypothetical proteins also have roles in microbial interactions by affecting the expression, regulation or function of other proteins in the host or the microbiome [21, 22]. Some methods to predict the function of hypothetical proteins using big data and machine learning are based on clustering the proteins based on their sequence similarity or interaction patterns [20, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Hypothetical proteins also have roles in microbial interactions by affecting the expression, regulation or function of other proteins in the host or the microbiome [21, 22]. Some methods to predict the function of hypothetical proteins using big data and machine learning are based on clustering the proteins based on their sequence similarity or interaction patterns [20, 22].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, protein is one of the essential elements for maintaining basic functions and processes in humans. Therefore, excessive protein restriction is not advised for the prevention of early renal function decline [ 17 ]. We prefer the regulation of intestinal flora and reducing pathogenic effects of endotoxin as possible effective managing strategies for DKD.…”
Section: Introductionmentioning
confidence: 99%